2019
DOI: 10.1016/j.visres.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Is blur sensitivity altered in children with progressive myopia?

Abstract: School aged children with progressive myopia show large lags in their accommodation and suggestive of a large depth of focus (DOF). While DOF measures are lacking in this age group, their blur detection and discrimination capacities appear to be similar to their non-myopic peers. Accordingly, the current study quantified DOF and blur detection ability in progressive myopic children showing large accommodative lags, compared to their non-myopic peers and adults.Blur sensitivity measures were taken from 12 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The external validity of these results to visually symptomatic individuals and during longer near tasks requires further investigation, since the experimental sample of the current study was formed by visually asymptomatic young adults and the near task was relatively short. Lastly, most investigations with MiSight lenses have been conducted in children, and it will be of interest to assess visual performance and comfort in this population, as children have different blur sensitivity than adults [59].…”
Section: Discussionmentioning
confidence: 99%
“…The external validity of these results to visually symptomatic individuals and during longer near tasks requires further investigation, since the experimental sample of the current study was formed by visually asymptomatic young adults and the near task was relatively short. Lastly, most investigations with MiSight lenses have been conducted in children, and it will be of interest to assess visual performance and comfort in this population, as children have different blur sensitivity than adults [59].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the variations in BDTs are due to blur adaptation, which could be induced by blur perception. Labhishetty et al (2019) found there were no significant differences in BDTs between progressive myopic children and their non-myopic peers, which could be explained by compensation in higher visual processes for poor retinal image quality. Hence, the amount of BDT variations induced by additional blur caused by Ortho-K treatment was small, however, the difference is significant because the measurements are quite repeatable and precise.…”
Section: Discussionmentioning
confidence: 60%
“…We speculate that the decreased accommodative lag is induced by blur adaptation, which is caused by the deterioration in visual quality following Ortho-K in children. The presence of similar BDTs in myopic and emmetropic children but a larger accommodative lag in myopic eyes means the low sensitivity to defocus could be compensated by some form of an adjustment in the higher visual processes (i.e., blur adaptation) to preserve or increase the subjective perception (Labhishetty et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Progressing myopes have large accommodative lags, micro‐fluctuations and an increased depth of focus, compared to non‐myopes, but similar blur detection thresholds. Therefore, progressing myopes seem to be less sensitive to retinal defocus, but this is compensated by some form of an adjustment in the higher visual processes to preserve the subjective percept, even when receiving poor retinal image quality . This cortical processing seems to override retinal defocus in those for whom the emmetropisation process has been compromised by a mismatch between the optical power of the eye and its axial length.…”
Section: Discussionmentioning
confidence: 99%